Thermodynamics of formation liquid interlayers in composite materials - Lisovsky, A.F.; Davidenko, S.A. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2019)
Composite materials consisting of refractory particles and a low-melting binder have been studied. In a composite body the process of the liquid outflow from a capillary into the body bulk have been described in terms of thermodynamics. An equation for the variation of the Helmholtz free energy of a microdispersed system during this process has been derived and the conditions, under which the liquid interlayers are either stable or unstable in the bulk of a composite body, have been established.